The impact of corporate income tax on capital structure and dividend policy decisions: an empirical study of listed firms in Malaysia - Hidajat, Joan (2019)
This study aims to investigate the impact of corporate income tax on firm’s capital structure and dividend policy decision by using a panel data made of 160 companies listed in Bursa Malaysia from 2008 to 2016, which made up a total of 1,440 observations. The listed companies are chosen from four different sectors including consumer products, industrial products, trading-services, and properties sector. The panel data in this study is analyzed using three methods, which are Pooled Ordinary Least Squares model, Random Effects Model, and Fixed Effects Model. The empirical analysis of this study is based on the results from Fixed Effects Model. This study also analyzed other factors such as profitability, asset tangibility, liquidity, non-debt tax shields, and firms’ size. Corporate income tax is found to have an insignificant negative influence on capital structure decision of Malaysian listed firms. On the other hand, it was found to have a significant negative impact on dividend policy decision of Malaysian firms. More relationships were discovered for other factors, where asset tangibility, liquidity, profitability, and firm size are found to be the key determinants on making capital structure decision, except for non-debt tax shields. However, only profitability and firm size are found to have significant impact on the dividend policy decision of Malaysian listed firms as other factors, such as asset tangibility, liquidity, and non-debt tax shields, are found to be statistically insignificant on dividend policy.